The Clinical Laboratory Findings and Complications of Malaria at District Shaheed Benazir Abad - Raiz Ahmed Qazi, Muhammad Muqeem Mangi, Lubna Siddique, Hira Saeed Khan, Maqbool Ahmed Mangi, Munza Noor Mangi, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To analyses the clinical as well as laboratory findings among patients with malaria. We also highlight the complications of malaria such as hypoglycemia and thrombocytopenia. Material and Methods: An experimental and descriptive study was conducted from March 2021 to September 2021 at the pathology department of the diagnostic and research laboratory of Peoples University of health sciences (PUMHS) Nawabshah. The frequency of haematological complications including anaemia, leukocytosis and thrombocytopenia among 1230 patients with malaria visiting OPO were studied. Malaria and its haematological complications were diagnosed on the bases of clinical and laboratory findings. Results: Out of 1230 patients, 820 (66.7%) were belonging to the suburbs and 410 (33.3%) were belonging to the city. The age range of the individuals in the study, comprising both children and adults, was from 5 - 65 years, with an average age of 35±30 years. The male-to-female ratio among these patients was 1.8:1. Malaria diagnosis was confirmed through both clinical observations and laboratory test results. The incidence of haematological complications, such as anaemia, leukocytosis, and thrombocytopenia, was evaluated using haematological measures, including the determination of Hemoglobin attentiveness and Complete Blood Count (CBC), in malaria patients. Conclusion: Malaria often leads to urgent treatment is necessary due to common hematological complications such as anemia, leukocytosis, and thrombocytopenia. Keywords: Malaria, frequency, hematological complications, hematological parameters